KEMAMPUAN MEMBACA PERMULAAN PESERTA DIDIK KELAS 3A SDN 02 PALEMBANG - Ulfa Fadilah; Vina Amilia Suganda M.; Dwi Cahaya Nurani (Jurnal Literasi Pendidikan Dasar, 2023)
This study aims to analyze the beginning reading ability of class 3A students at SDN 02 Palembang, South Sumatra. The method used by researchers is descriptive qualitative with data collection techniques through observation and interviews with class 3A students at SDN 02 Palembang. The results showed that many students still could not read fluently and did not understand the meaning of the words or sentences that were read. Researchers consider that students rely more on sound in learning, they can remember what other people read, and can remember if it is read repeatedly. The results of the study show that internal factors such as interest and tenacity, as well as external factors such as the learning environment and parental support, play an important role in reducing initial reading difficulties in students, especially for students who are already in grade 3 of elementary school.